IMPLEMENTASI KERJA SAMA INDONESIA-AMERIKA SERIKAT DALAM COUNTER TERRORISM: HASIL PROGRAM DIPLOMATIC SECURITY SERVICE ANTITERRORISM ASSISTANCE TERHADAP KASUS TERORISME DI INDONESIA TAHUN 2003-2014 - Harwanto, Aji Tito; Utomo, Tri Cahyo; Hanura, Marten (Journal of International Relations, 2016)
Since the events of 9/11 were carried out Al-Qaeda group in the United States,the world back on to remind you that the crime of terrorism can be doneanytime and anywhere. Al-Qaeda group led by Osama bin Laden wanted toattack the United States and its allies to fight the oppression of Muslims bydeveloping a network to Indonesia. Groups in Indonesia who are convicted ofterrorism and has a style of thinking is similar to Al-Qaeda, namely JamaahIslamiyah, Jemaah Ansharut Tauhid, East Indonesian Mujahedeen and WestIndonesian Mujaheddin. In response to the terrorist acts, Indonesia incooperation with the United States to train law enforcement personnel of theRepublic of Indonesia is in the DSS/ATA (Diplomatic Security ServiceAntiterrorism Assistance). Literature and interviewing is a method to knowthe progress of the implementation of the cooperation. The initial results ofthis study showed that less than the maximum implementation of thiscooperation because there is some training that is not in its implementation.Then it can be concluded that the initial results of the study showed a negativecorrelation with the end result of research which states that the cooperationin the program DSS/ATA has been running well since the training has notbeen implemented yet due to terrorism cases should be dealt with using thetraining. After analysis, the authors also provide recommendations forcooperation between Indonesia and the United States in the DSS/ATA